A Molecular Survey of Rickettsias in Shelter Dogs and Distribution of Rhipicephalus sanguineus (Acari: Ixodidae) sensu lato in Southeast Turkey - Ozubek, Sezayi; Ipek, Duygu Neval Sayin; Aktas, Munir (Oxford Univ Press Inc, 2018)
Canine tick-borne pathogens are the source of emerging diseases and have important zoonotic relevance. Dogs play a major role in the transmission of several zoonotic tick-borne pathogens, as reservoirs and/or sentinels. To simultaneously detect Anaplasma and Ehrlichia species, a reverse line blot assay was conducted on 219 blood samples collected from autochthonous asymptomatic shelter dogs. One hundred and three (47.0%, CI 40.3-53.9) dogs were positive for one or both rickettsial pathogens. Seventy-one (32.4%, CI 26.3-39.0) dogs were infected with Anaplasma platys and 23 (10.5%, CI 6.8-15.3) with Ehrlichia canis. Concurrent infection with A. platys and E. canis was detected in nine (4.1%, CI 1.9-7.6) dogs. Partial sequences of the 16S ribosomal RNA gene shared 100% identity with the corresponding published sequences for A. platys and E. canis. Infection with Anaplasma phagocytophilum was not detected in the examined dogs. In total, 1018 (range 1-70, mean intensity 13.1, mean abundance 4.6) Rhipicephalus sanguineus (Latreille) (Acari: Ixodidae) sensu lato ticks (45.7% nymphs, 54.3% adults) were collected from the dogs. There was no significant association between Anaplasma/Ehrlichia infection and dog sex or age, but a significant correlation was found between rickettsia infection and presence of R. sanguineus. Improved tick control strategies to reduce the risk of these pathogens spreading among dogs and humans are needed in the region.
Keywords: Anaplasma platys; Ehrlichia canis; Rhipicephalus sanguineus sensu lato; dog; Reverse line blot